2017
DOI: 10.5194/tc-11-2919-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of snow grain shape on climate simulations: sensitivity tests with the Norwegian Earth System Model

Abstract: Abstract. Snow consists of non-spherical grains of various shapes and sizes. Still, in radiative transfer calculations, snow grains are often treated as spherical. This also applies to the computation of snow albedo in the Snow, Ice, and Aerosol Radiation (SNICAR) model and in the Los Alamos sea ice model, version 4 (CICE4), both of which are employed in the Community Earth System Model and in the Norwegian Earth System Model (NorESM). In this study, we evaluate the effect of snow grain shape on climate simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…This is because the four subregions (NETP, SETP, CTP, and HIMA) are dominated by the strong BC emissions in the non-monsoon season (particularly winter and spring) over South and East Asia (Lu et al, 2012;Zhang et al, 2015;Yang et al, 2018) and the efficient wet removal of BC in Asia in the monsoon season (Xu et al, 2009;He et al, 2014a). In contrast, the high concentrations during the monsoon period over NWTP and NOTP are primarily caused by the enrichment of BC via sublimation and/or melting of snow (Ming et al, 2009;Yang et al, 2015) and emissions from Central Asia and Middle East (Kopacz et al, 2011;Schmale et al, 2017).…”
Section: Bc Observations In the Tibetan Snowpackmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the four subregions (NETP, SETP, CTP, and HIMA) are dominated by the strong BC emissions in the non-monsoon season (particularly winter and spring) over South and East Asia (Lu et al, 2012;Zhang et al, 2015;Yang et al, 2018) and the efficient wet removal of BC in Asia in the monsoon season (Xu et al, 2009;He et al, 2014a). In contrast, the high concentrations during the monsoon period over NWTP and NOTP are primarily caused by the enrichment of BC via sublimation and/or melting of snow (Ming et al, 2009;Yang et al, 2015) and emissions from Central Asia and Middle East (Kopacz et al, 2011;Schmale et al, 2017).…”
Section: Bc Observations In the Tibetan Snowpackmentioning
confidence: 99%
“…To estimate BC-induced snow albedo effects over the TP, previous studies often used observed BC concentrations in snow/ice as inputs to snow albedo models by assuming spherical snow grains and BC-snow external mixing (e.g., Ming et al, 2013;Jacobi et al, 2015;Schmale et al, 2017;Zhang et al, 2018). This simplified treatment of BC-snow interactions has been widely used in snow albedo modeling over various snow-covered regions (e.g., Warren and Wiscombe, 1980;Aoki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Snow albedo is an important part of the energy cycle and at least in global climate models, the simulated temperature can be quite sensitive to relatively small changes in snow albedo (e.g., Räisänen et al, 2017). Lakes in the Nordic countries are usually always covered with snow during winter.…”
Section: The Snow Albedomentioning
confidence: 99%
“…Black carbon (BC), the most important light‐absorbing aerosol (Bond et al, ), has been observed as a strong driver to accelerated glacier retreat and snowmelt over high mountains (Di Mauro et al, ; Painter et al, ), midlatitude seasonal snowpack (Sterle et al, ; Wang et al, ), and polar regions (McConnell et al, ; Pedersen et al, ). The impacts of BC on snow albedo can be affected by a number of factors, including BC content in snow, BC and snow particle properties, and environmental conditions (e.g., He et al, ; He, Takano, & Liou, ; Kokhanovsky, ; Räisänen et al, ; Warren & Wiscombe, ). Thus, accurate predictions of BC effects on snow albedo and regional climate require comprehensive understanding and quantification that integrates these key factors.…”
Section: Introductionmentioning
confidence: 99%